2018
DOI: 10.1088/2058-6272/aab491
|View full text |Cite
|
Sign up to set email alerts
|

Dust acoustic shock waves in magnetized dusty plasma

Abstract: We have presented a theoretical study of the dust acoustic (DA) shock structures in a magnetized, electron depleted dusty plasma in the presence of two temperature superthermal ions. By deriving a Korteweg-de Vries-Burgers equation and studying its shock solution, we aim to highlight the effects of magnetic field and obliqueness on various properties of the DA shock structures in the presence of kappa-distributed two temperature ion population. The present model is motivated by the observations of Geotail spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…in magnetised/unmagnetised space dusty plasmas in the framework of reductive 0123456789(). : V,-vol perturbation approach and Sagdeev pseudopotential method [10][11][12][13][14][15][16][17][18][19]. Due to the large size of the dust grains, electrons can stick to the dust grain surface.…”
Section: Introductionmentioning
confidence: 99%
“…in magnetised/unmagnetised space dusty plasmas in the framework of reductive 0123456789(). : V,-vol perturbation approach and Sagdeev pseudopotential method [10][11][12][13][14][15][16][17][18][19]. Due to the large size of the dust grains, electrons can stick to the dust grain surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, the minimum value of n e0 /n i0 > m e /m i for T e ≈ T i , where m e (T e ) is the electron mass (temperature). The process of electron depletion has been identified by laboratory experiments and space observations, and successively has been considered by many researchers [33,34,35,36,37] to study the effects of the electron depletion in modifying the electrostatic potential structure in DPM. Sahu and Tribeche [1] examined the non-planar DA shock waves (DASHWs) in an electron depleted DPM (ED-DPM) in presence of non-extensive ions, and found that the DA solitons may exhibit rarefaction and compression for q > 0 and q < 0, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Shahmansouri and Alinejad [6] analyzed DA solitary waves (DASWs) in a magnetized EDDPM. Ghai et al [34] reported a theoretical analysis on the DASHW structure regarding an electron depleted plasma system. Shahmansouri and Tribeche [35] studied the DA double-layers and DASWs in EDDPM having two temperature super-thermal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Spacecraft and satellite observations revealed the fact the charged particles in astrophysical and space environments are very far from the thermodynamic equilibrium due to their extremely high temperature and low densities. These high energetic plasma particles follow the non-Maxwellian distribution like generalized Lorentzin distribution (kappa distribution) [24,25]. The density of high energetic plasma particles like electrons following superthermal kappa distribution can be given by [26,27] where is called the spectral index parameter, and if → ∞ , this distribution goes to Maxwellian distribution.…”
Section: Introductionmentioning
confidence: 99%